Exploration of post-PEG precipitation TSH recovery in hypothyroid patients - Yin, Jing; Mei, Zhanjun; Zhang, Bo; Tang, Fang (Frontiers in Endocrinology, 2025)
IntroductionThyroid disorders are among the most common endocrine diseases, and their diagnosis and monitoring rely heavily on laboratory testing. However, immunoassays used to assess thyroid function are susceptible to various types of interference, which can affect clinical decision-making. This study aimed to establish a novel method for evaluating the potential interference of serum macromolecules in the detection of Thyroid Stimulating Hormone (TSH).Materials and methodsA total of 160 patients (87 with hypothyroidism and 73 with subclinical hypothyroidism) from the Nuclear Industry 416 Hospital between July 1, 2023 and November 30, 2023, were enrolled as the experimental group. Additionally, 160 healthy individuals were randomly selected from the health examination center as the control group. Samples were treated using polyethylene glycol (PEG) precipitation method, and TSH recovery rates were calculated.ResultsSignificant differences in TSH recovery rates were observed among the hypothyroidism group (35.0% ± 13.3%), subclinical hypothyroidism group (30.1% ± 7.9%), and control group (56.9% ± 12.4%) (P< 0.05). A TSH recovery rate cutoff-value of 28% was established. The incidence of macromolecular interference was 36.6% in the hypothyroidism group and 39.7% in the subclinical hypothyroidism group, with no significant difference between the two groups (P = 0.771). All control group participants had TSH recovery rates >28%. In hypothyroid samples with TSH recovery rates<28%, a positive correlation was found between TSH recovery and FT3 levels (P = 0.027, Pearson correlation coefficient = 0.396).ConclusionsThis study provides a new reference for the clinical evaluation of TSH. When TSH recovery rates are below 28% in patients with hypothyroidism or subclinical hypothyroidism, the presence of serum macromolecules should be considered.